La moda, Jano en movimiento: novedad y muerte en la aceleración del tiempo moderno (El Hilo de la Fabula, 2022)
Through the concept and the phenomenon of fashion, this article is aimed at  focusing on the articulation between novelty and the outdated as a sequence that is key to understanding the existence of the human and the non-human in the society of capitalist acceleration. The problematic is developed on the basis of Leopardi's operetta, Dialogue of Fashion and Death. Novelty and death belong to the grammar of fashion, which the enlightened figure of progress threads into transience as the very form of its historical production. Leopardi’s Dialogue has its continuity both in the literature of Rilke and in the positions of Baudelaire, Tarde, Simmel and Benjamin. The passage from the materialization of fashion to its morphology reveals itself as the accelerated flight of time, which manifests itself in the ephemerality of capitalist mercantile fetishism. Fashion succeeds in transforming acceleration into habit, even at the cost of life itself, pushing existence into an infernal destiny.
Keywords: European Literature; Fashion; Death; Modernity; Capitalism